2020
DOI: 10.1111/liv.14373
|View full text |Cite
|
Sign up to set email alerts
|

Baveno VI and Expanded Baveno VI criteria successfully predicts the absence of high‐risk gastro‐oesophageal varices in a Chilean cohort

Abstract: Background: Baveno VI and expanded Baveno VI criteria have been recommended to circumvent the need for endoscopy screening in patients with a very low probability of varices needing treatment (VNT). Aim:To validate these criteria in a Latin American population. Methods:The ability of Baveno VI criteria (liver stiffness measurement (LSM) <20 kPa and platelet count >150 × 103/μL) and expanded Baveno VI criteria (LSM < 25kPa and platelet count >110 × 103/μL) to exclude the presence of VNT was tested in a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…The Baveno VI consensus recommended avoiding gastroscopy when LSM < 20 kPa and PLT > 150,000/L. Our study also validated the effectiveness and safety of the B6C, which was consistent with other published literatures 23,[33][34][35] . However, the number of patients who can benefit from the B6C was still small, and our results shown that it was only 27.7%.…”
Section: Discussionsupporting
confidence: 91%
“…The Baveno VI consensus recommended avoiding gastroscopy when LSM < 20 kPa and PLT > 150,000/L. Our study also validated the effectiveness and safety of the B6C, which was consistent with other published literatures 23,[33][34][35] . However, the number of patients who can benefit from the B6C was still small, and our results shown that it was only 27.7%.…”
Section: Discussionsupporting
confidence: 91%
“…The Expanded Baveno VI criteria would have spared 23.3% of unnecessary EGDs and missed 4.8% of HRV. The number of spared EGDs is lower than the number reported in previous studies [7,13,14,19]. The lower number of spared EGDs may be explained by the bias in selection of patients and the high prevalence of HRV, which may have led to a low NPV and influenced the diagnostic performance [18].…”
Section: Discussionmentioning
confidence: 73%
“…TE was only available for the Beijing cohort. LSM was assessed according to the manufacturer's FibroScan standard procedure [ 14 , 15 ], performed by one expert operator (Li Li) at Beijing Shijitan Hospital (>100 procedures). LSM was considered valid when there were at least 10 measurements with an interquartile range to median ratio (IQR/M) ≤ 30% [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in the recent study [14] , the American Liver Research Association proposed a new standard that endoscopy is not required when the LSM< 25kpa and the PLT>110×10 9 /L. Subsequently, different studies veri ed the diagnostic value of the two standards [15] . In a study of 1035 patients with compensatory advanced chronic liver disease, the extended standard (51.7%) could avoid more endoscopy than the original standard (27.6%), but the extended standard also missed more high-risk varices (6.8%, 3.8%).…”
Section: Discussionmentioning
confidence: 99%